الشخصية العجائبية في رواية البئر الكوني - زيتوني, فاطمة (كلية الأدب العربي والفنون, 2024)
يدرس هذا البحث ملامح الشخصية العجائبية في سرد الروائي الليبي إبراهيم الكوني من خلال روايته "البئر" وهي الحركة الأولى من رباعية الخسوف والتي تعدد حضور الشخصية فيها من شخصيات عادية وشخصيات عجائبية محضة، كما تجلى ذلك في شخصية "تانس"، هذه الشخصيات لها أشكالها ووظائفها وأبعادها التي إستمدت عجائبيتها من الأسطورة والحكايات الشعبية التي جعلتها تصنف ضمن الأدب الخوارقي الذي يبعث الحيرة والدهشة مما جعل الكوني يستثمره في روايته لدمج الحاضر بالأسطورة لبناء عالم وفق رؤيا مغايرة للواقع This research studies the formations of the miraculous character in the narrative of the Libyan novelist Ibrahim Al-Koni through his novel “The Well” which is the first movement of the Eclipse Quartet, in which the presence of the character is numerous, from ordinary characters to purely miraculous characters with their own forms, functions, and dimensions that derive their miraculousness from myth and folk tales that made them classified among... Paranormal literature, which inspires confusion and astonishment, is what made Al-Koni invest in his novel to merge the present with myth to build a world according to a vision different from reality.
Keywords: الشخصية العجائبية، رّواية البئر، الأدب الخوارقي، الأسطورة; the miraculous character, the well novel, paranormal literature, myth.